PERANCANGAN BEBAN DORONG PADA BOX UNDERPASS - Sulardi, Sulardi; Prasetyo, Sigit Dwi (Jurnal Ilmiah Desain & Konstruksi, 2014)
This Sincetific work about box underpass design has a purpose to design box underpass and design jacking force for box underpass indtallation. The method of box underpass designing is ultimate design method. Box underpass designed for a 60 cm thick for top slab, foundation slab, and wall plates. And used K-500 quality of concrete, and BjTD 40 quality of reinforcement steel. In this case, structural analysis performed using moment distribution method. Moment, shear, and axial force is used to calculate the reinforcement and control of serviceability. For top slab, main bar used is D36 – 200, while support bar used is D22 – 300. For the foundation slab, main bar used is D36 - 250, while support bar used is D22 – 350. For the wall plate, the main bar used was D32 - 200, support bar used is D19 - 350, while the shear bar used is D19 - 500. For one box underpass installation with 9,3 m length into the soil needed jacking force greater than 8190,185 kN. And for add one span box underpass, required additional jacking force around 4726,583kN. Keywords: Box Underpass, Concrete, Reinforcement, Jacking Force